2018
DOI: 10.1063/1.5030099
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized patterns by a DC pin liquid anode discharge in ambient air: Effect of liquid types on formation

Abstract: A pin liquid anode DC discharge is generated in open air without any additional gas feeding to form self-organized patterns (SOPs) on various liquid interfaces. Axially resolved emission spectra of the whole discharge reveal that the selforganized patterns are formed below a dark region and are visible mainly due to the N2 (C 3 -B 3 ) transitions. The high energy N2 (C) level is mainly excited by the impact of electrons heated by the local increased electric field at the interface. For the first time, the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 78 publications
4
30
0
Order By: Relevance
“…However, under water anode conditions, the discharge is glow, and the plasma is diffuse. Zhang et al [36] investigated the structure and properties of an air discharge in contact with various electrolytes (water with HCl, HF, or H 2 SO 4 ), and they always observed a dark zone above the electrolyte surface, irrespective of its nature. The observations of Zhang et al [36] are consistent with those of Liu et al [30], as well as with the ICCD images recorded herein under anode water polarity conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under water anode conditions, the discharge is glow, and the plasma is diffuse. Zhang et al [36] investigated the structure and properties of an air discharge in contact with various electrolytes (water with HCl, HF, or H 2 SO 4 ), and they always observed a dark zone above the electrolyte surface, irrespective of its nature. The observations of Zhang et al [36] are consistent with those of Liu et al [30], as well as with the ICCD images recorded herein under anode water polarity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental analysis of these emission patterns is of great importance due to their effect on the local production and transport of reactive species. The mechanisms involved in the structuration process are not well understood; however, it has been established that oxygen species [34], injected power [30,32], water polarity [35], and other water properties (composition, acidity, conductivity) [36] play an essential role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…A slight increase in the plasma length brings about significant pattern changes in the morphology, as shown on the far‐right side of Figure 6a. Because gap distance is another major factor affecting SOPs, [ 9 ] we moved on to study the pattern formation and plasma properties at different gap distances.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments carried out for self-organization using liquid electrodes have reported that pattern formation depends on operating condition parameters such as discharge current, gas flow rate, gap distance, conductivity, anode polarity of the liquid, and liquid types. [1][2][3][4][5][6][7][8][9][10] These parameters can also cause changes in the plasma. Exploring the changes in the physical properties of the plasma in these processes can help gain a deeper understanding of pattern formation.…”
mentioning
confidence: 99%
“…In physics, many examples illustrate selforganization processes, including arrangement of ferromagnetic objects and films [27,28] , quantum particles at zero temperature in optical lattice [29] , systems near the rigidity percolation threshold [30] , etc. In the specific research field of cold plasma physics, selforganized patterns have also been highlighted in cathode boundary layer micro-discharges [31] , DC pin electrodes interacting with liquids [ 32] , high power impulse magnetron sputtering [33] .…”
Section: Self-organizationmentioning
confidence: 99%